Reactivity study and biological activity of diterpenes from Plectranthus spp. - Borozan, Anastasia (2020)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2017